Aprendendo a ser autor da ação empreendedora: narrativas compartilhadas e situadas no alto sertão paraibano - Rodrigues, Danilo Gonçalves (2017)
This study has as main objective to understand the situated learning process of entrepreneurs of the city of Cajazeiras (PB) as authors of their entrepreneurial action. Thus, we tried to describe the shared narratives of the personal and professional trajectories of entrepreneurs of the city of Cajazeiras (PB); identify the constituent elements of entrepreneurial action; characterize the situated learning of the entrepreneurs; and outline the development of the authorship of entrepreneurial action. The research is based on the theoretical knowledge (a) of the entrepreneurial action as an individual and relational agency, rooted in a social context; (b) situational, contextual and relational entrepreneurial learning; And (c) entrepreneurial authorship developed through interactive and reflective relationships, and responsible for the cooperative creation of a socially recognized identity. Narrative was the main research strategy used. Eleven individuals were interviewed, besides the entrepreneur, who are part of the personal and professional network of this subject. The results reveal the entrepreneurial authorship as a competence based on the situated action, learning and narrative of the entrepreneurs. This authorship is built through the contextual, professional and personal immersion of the entrepreneur in the mileu in which it is situated. This mileu is infused with individual and collective meanings and actions that will be (re) built throughout the life of the entrepreneur through his living together with family, friends, business partners, employees, the community in general, and especially with mentors. To facilitate comprehension, the analysis was performed in a way to interpret each objective at a time. Thus, one perceives the life narrative of an author-entrepreneur marked by the shared understanding of his own self, of the critical events and the contextualization of these moments; The entrepreneurial action as being formed by collective actions of diverse social institutions and agents, the feeling and situation of rooting and the own entrepreneurial agency; Entrepreneurial learning as marked by personal situated theories, by cultural participation, relational and interactive learning, professional and sectoral immersion, by doing and reflecting and by the recognition of error; And, entrepreneurial authorship as a competence constituted of collective construction, maturity, protagonism and authorial identity. With this, entrepreneurial authorship is understood as being developed throughout the life of the entrepreneur by the learning situated and exercised daily by his entrepreneurial action.